2009
DOI: 10.1111/j.1365-2818.2009.03154.x
|View full text |Cite
|
Sign up to set email alerts
|

Disassembly of DNA–ligand on mica surface: atomic force microscopy studies

Abstract: SummaryDisassembly of DNA-ligands, including DNA-methylene blue (MB) complex and DNA-Co(phen) 3 3+ complex on mica surface, were investigated by atomic force microscopy (AFM). The disassembly of these complexes occurred after they were immersed in ultra-pure water. AFM results showed that the disassembly depended strongly on bridge ions that were used to immobilize the complex onto mica surface, DNA species and ligands. When Mg 2+ was used as the bridge ion, the DNA-MB complex was completely disassembled becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…We found that β progressively decreased with the incubation time whether or not free EcoRI was present in solution (Figure ). In agreement with a recent study, this result indicates that EcoRI irreversibly dissociates from its specific DNA site on the mica surface under strong adsorption conditions.…”
Section: Resultssupporting
confidence: 93%
“…We found that β progressively decreased with the incubation time whether or not free EcoRI was present in solution (Figure ). In agreement with a recent study, this result indicates that EcoRI irreversibly dissociates from its specific DNA site on the mica surface under strong adsorption conditions.…”
Section: Resultssupporting
confidence: 93%